The impact of early life family structure on adult social attachment, alloparental behavior, and the neuropeptide systems regulating affiliative behaviors in the monogamous prairie vole (Microtus ochrogaster) - Ahern, Todd H.; Young, Larry J. (Frontiers in Behavioral Neuroscience, 2009)
Early social attachments lie at the heart of emotional and social development in many mammals, including humans. In nature, monogamous prairie voles (Microtus ochrogaster) experience considerable natural variation in early social attachment opportunities due to differences in family structure (e.g., single-mothers, solitary breeding pairs, and communal groups). We exploited some of this natural variation in family structure to examine the influence of early social environment on the development of adult social behavior. First, we characterized the parental care received by pups reared biparentally (BP) or by a single-mother (SM) in the laboratory. Second, we examined whether BP- and SM-reared offspring differed in adult nurturing, bonding, and emotional behaviors. Finally, we investigated the effects of rearing condition on neuropeptide systems that regulate adult social behavior (oxytocin, vasopressin, and corticotropin-releasing factor [CRF]). Observations revealed that SM-reared pups were exposed more frequently (P<0.01), licked and groomed less (P<0.01), and matured more slowly (P<0.01) than BP-reared pups. In adulthood, there were striking socio-behavioral differences: SM-reared females showed low spontaneous, pup-directed alloparental behavior (P<0.01) and both males and females from the SM-reared condition showed delayed partner preference formation. While rearing did not impact neuropeptide receptor densities in the ventral forebrain as we predicted, SM-reared animals, particularly females, had increased OT content (P<0.01) and greater dorsal raphe CRF2 densities (P<0.05) and both measures correlated with licking and grooming experienced during the first 10 days of life. These results suggest that naturalistic variation in social rearing conditions can introduce diversity into adult nurturing and attachment behaviors.